Bio-remediation capacity for Cd(II) and Pb(II) from the aqueous medium by two novel strains of microalgae and their effect on lipidomics and metabolomics. (December 2021) - Nanda, Manisha; Jaiswal, Krishna Kumar; Kumar, Vinod; Verma, Monu; Vlaskin, Mikhail S.; Gururani, Prateek; Kim, Hyunook; Alajmi, Mohamed Fahad; Hussain, Afzal
Abstract: Microalgae have been the subject of recent research as a sustainable feedstock for the large-scale production of metabolites for commercial purposes. This study presents a green bio-remediation approach towards heavy metal contaminations and biomass production for biofuels in microalgae metabolomics and lipidomics approaches. Two novel microalgae, Chlorosarcinopsis bastropiensis and Polyedriopsis spinulosa, were isolated during the study and subjected to Pb(II) and Cd(II) pollutants. The isolated microalgae strains have shown a varied behavior towards cell growth, pigment accumulation, and lipids profiles during the impact of short-term (96 h) and long-term (14 d) heavy metal tolerance. Cell viability and IC50 value (397.75 mg/L for C. bastropiensis and 490.16 mg/L for P. spinulosa ) have indicated higher tolerance towards Pb(II) in both microalgae. FTIR analysis of microalgal biomass has revealed insignificant differences during long and short-term heavy metal toxicity, clearly indicating the bio-tolerance for Pb(II) and Cd(II) in both microalgae. Principal component analysis has revealed the expression of metabolites (such as glycine, proline, valine, isoleucine, linoleic acid, glucose, sucrose, etc.) under heavy metal stress. 1 H NMR analysis has demonstrated the prominent expression of metabolites under heavy metal stress. ICP-MS-based studies do not reflect the correlation between cellular tolerance and bioaccumulation of each heavy metal by both microalgae. Lipidomics based on 1 H NMR has revealed an increase in unsaturated fatty acids under the impact of heavy metals. Therefore, this study offers a sustainable bioremediation technique for heavy metal contaminants and biomass production with significant enhancement of metabolites and lipid components for biofuels and/-or other commercial applications. Graphical abstract: Unlabelled Image Highlights: Novel green microalgae in the sustainable bioremediation of heavy metal pollutants Tolerance to Pb 2+ /Cd 2+ and biochemical profile in short (96 h) and long term (14 d) Principal component analysis revealed expression of metabolites under metals stress. 1 H NMR studies revealed elevated expression of metabolites under heavy metal stress. 1 H NMR-based lipidomics shown an increase in unsaturated fatty acids accumulation.